The Leadership of Military Organization in the Perspective Era of Industrial Revolution 4.0 - Amarulla Octavian, Marsetio, I Nengah Putra A. (International Journal of Advanced Science and Technology, 2020)
The reputation of military organizations is seen as an institution that is immune to evolution due to the policy constraints of doctrine and armed soldiers. However, the emergence of drastic and rapid technological changes in the era of the Industrial Revolution 4.0, forced the military to adapt more quickly and evolve to make major changes. The change also requires military organizations to face various forms of threats in modern warfare. To maintain its existence, the military is also required to fully exploit all resources to obtain economic and technological benefits arising from rapid changes in technological progress that is widely applicable. Military leadership must analyze the positive and negative results of the Industrial Revolution 4.0 as readiness to carry out various forms of modern warfare through adjusting organizational needs and readiness of human resources, intelligence, logistics, and operations. Faced with strategic environmental dynamics and geopolitical changes, military capabilities must be developed based on digital technology, big data, and artificial intelligence to face the opportunities and challenges of the Industrial Revolution era 4.0. Military organizations in the Industrial Revolution 4.0 era needed a Strategic model of leadership, Agile leadership, and Transformational leadership. Keywords: Industrial Revolution 4.0, Strategic Leadership, Agile Leadership, Transformational Leadership